2018
DOI: 10.1371/journal.pone.0191246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freeze-thaw cycling on grain size of biochar

Abstract: Biochar may improve soil hydrology by altering soil porosity, density, hydraulic conductivity, and water-holding capacity. These properties are associated with the grain size distributions of both soil and biochar, and therefore may change as biochar weathers. Here we report how freeze-thaw (F-T) cycling impacts the grain size of pine, mesquite, miscanthus, and sewage waste biochars under two drainage conditions: undrained (all biochars) and a gravity-drained experiment (mesquite biochar only). In the undraine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Some natural nano-sized particles may be mixed with biochar particles, wedging into their curvature surface, or even the porous structures. Because of their different expansion properties, biochars may be broken into smaller particles during the freeze-thawing cycles or dry-wet cycles (Liu et al 2018).…”
Section: Abiotic Aging and Physical Embedding Processesmentioning
confidence: 99%
“…Some natural nano-sized particles may be mixed with biochar particles, wedging into their curvature surface, or even the porous structures. Because of their different expansion properties, biochars may be broken into smaller particles during the freeze-thawing cycles or dry-wet cycles (Liu et al 2018).…”
Section: Abiotic Aging and Physical Embedding Processesmentioning
confidence: 99%
“…The time scale of biochar aging in the field varies from a few weeks to more than 10 years. ,, To accelerate and simulate the aging process, microbial, physical, and chemical aging , have been used previously. Microbial aging is carried out in both aerobic and anaerobic conditions, resulting in the release of mineralizable organic compounds that can be a carbon source for microorganisms. , Physical aging is typically achieved through fragmentation, erosion, air-drying, and alternating cycles of wetting–drying or freezing–thawing, , which leads to formation of fresh reactive surfaces and a decrease of biochar particle size.…”
Section: Introductionmentioning
confidence: 99%
“…The time scale of biochar aging in the field varies from a few weeks to more than 10 years. ,, To accelerate and simulate the aging process, microbial, physical, and chemical aging , have been used previously. Microbial aging is carried out in both aerobic and anaerobic conditions, resulting in the release of mineralizable organic compounds that can be a carbon source for microorganisms. , Physical aging is typically achieved through fragmentation, erosion, air-drying, and alternating cycles of wetting–drying or freezing–thawing, , which leads to formation of fresh reactive surfaces and a decrease of biochar particle size. Chemical aging often contributes to an increase of labile organic molecules, oxidation of certain minerals (e.g., magnetite), and/or oxygen-containing functional groups in biochar. ,, Previous studies showed that these aging methods changed the physicochemical properties of biochar, including labile organic compounds, specific surface area and porosity, element composition and molecular structure, anion/cation exchange capacity, , surface roughness and hydrophilicity, and enrichment of oxygen-containing functional groups .…”
Section: Introductionmentioning
confidence: 99%
“…High pyrolytic temperature in biochars generally translates to high pore volume and water holding capacity. 36 SEM imaging of SWP700 shows a highly porous framework consisting of macro-(Figures 1 and S2), meso-, and micropores, which could be penetrated by water transporting dissolved Hg(II) species. Recent studies using the same biochar show that 95% of the total porosity in SWP700 corresponds to a pore width of <3 μm, 37 with 1.4 and 7.8% consisting of micro-(<2 nm) and mesopores (2−50 nm), respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%